2017
DOI: 10.4103/ijpm.ijpm_204_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MUC1 and P53 expressions in noninvasive papillary urothelial neoplasms of bladder, their relationship with tumor grade and role in the differential diagnosis

Abstract: MUC1 and p53 may be helpful immunohistochemical markers for distinguishing PUNLMP from LGPUC and HGPUC, when the histologic signs are not obvious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Immunoreactivity was calculated using the following semiquantitative scale: 3+, 80‐100% positive epithelial cells with EM; 2+, 40‐80% positive epithelial cells with EM; 1+, 20‐40% positive epithelial cells with EM; and −, no reaction. Like other authors, we report two morphologic types of MUC1 expression: normal (apical/superficial) and aberrant (perinuclear/cytoplasmic/cytoplasm‐membrane). The specificity of staining was assessed using negative controls in which (i) the primary antibody was absent; (ii) the primary antibodies were replaced with 3% bovine serum albumin; and (iii) the primary antibodies were replaced with preimmune mouse serum.…”
Section: Methodssupporting
confidence: 86%
“…Immunoreactivity was calculated using the following semiquantitative scale: 3+, 80‐100% positive epithelial cells with EM; 2+, 40‐80% positive epithelial cells with EM; 1+, 20‐40% positive epithelial cells with EM; and −, no reaction. Like other authors, we report two morphologic types of MUC1 expression: normal (apical/superficial) and aberrant (perinuclear/cytoplasmic/cytoplasm‐membrane). The specificity of staining was assessed using negative controls in which (i) the primary antibody was absent; (ii) the primary antibodies were replaced with 3% bovine serum albumin; and (iii) the primary antibodies were replaced with preimmune mouse serum.…”
Section: Methodssupporting
confidence: 86%
“…As we also demonstrated that high levels of MUC1 expression were confirmed in the tumor surface, especially in Ta/is/1 tumor, MUC1 expression might be informative for the cytological diagnosis and the combination of cytology and MUC1 has a potential to detect more UC cases. In fact, Kaymaz et al reported that MUC1 and p53 expression are useful for the diagnosis of noninvasive papillary urothelial neoplasms in BC tissues 21 . Terauchi et al revealed that intracytoplasmic lumina in urine cytology is important for the diagnosis of high‐grade UC and for predicting a poor prognosis, and it is associated with MUC1 expression 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Kaymaz et al reported that MUC1 and p53 expression are useful for the diagnosis of noninvasive papillary urothelial neoplasms in BC tissues. 21 Terauchi et al revealed that intracytoplasmic lumina in urine cytology is important for the diagnosis of high-grade UC and for predicting a poor prognosis, and it is associated with MUC1 expression. 46 These findings indicate that MUC1 expression has potential application as a diagnostic immunomarker for UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies suggest multiple signaling pathways are involved in BC progression ( 3 , 4 ), however, specific mechanisms of BC etiology are still unknown. Due to invasive and costly procedures such as cystoscopy, researchers are exploring potential biomarkers from either urine or peripheral blood ( 5 , 6 ). Consequently, investigation of novel noninvasive biomarkers to enhance the early detection of BC is of great importance.…”
Section: Introductionmentioning
confidence: 99%